2021
DOI: 10.48550/arxiv.2103.14956
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dark Patterns in the Interaction with Cookie Banners

Philip Hausner,
Michael Gertz

Abstract: Dark patterns are interface designs that nudge users towards behavior that is against their best interests. Since humans are often not even aware that they are influenced by these malicious patterns, research has to identify ways to protect web users against them. One approach to this is the automatic detection of dark patterns which enables the development of tools that are able to protect users by proactively warning them in cases where they face a dark pattern. In this paper, we present ongoing work in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Dark patterns are tricky because "It is rarely possible to foresee which new patterns are going to emerge, and as a result, detection measures are always reactive, and rely on practitioners that constantly update the existing pattern databases as well as engaged consumers that point out new occurrences". (Hausner and Gertz, 2021). Thus, guidelines may need to be continuously updated and limited to a particular context of use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dark patterns are tricky because "It is rarely possible to foresee which new patterns are going to emerge, and as a result, detection measures are always reactive, and rely on practitioners that constantly update the existing pattern databases as well as engaged consumers that point out new occurrences". (Hausner and Gertz, 2021). Thus, guidelines may need to be continuously updated and limited to a particular context of use.…”
Section: Discussionmentioning
confidence: 99%
“…Text, compared to image, is harder to automatically scrap from online applications, particularly if the interface interaction invokes other interfaces. Cookie banners are observed to employ legal and technical jargon (Strycharz et al, 2021;, vague and ambiguous language (Santos et al, 2017), and positive or negative framing (Hausner and Gertz, 2021) which hampers automatic detection of textual expressions. An open question is whether the text of the interface is sufficient to identify a dark pattern.…”
Section: Representation Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it has been shown that users tend to ignore privacy-related notices [22,32,54]. Considering GDPR Privacy Banners, users tend to accept privacy policies when offered a default button via intrusive banners that nudge users [18,27], which is often the case [33] with websites offering large pop-ups or wall-style banners that cover most of the webpage as seen in Figure 1.…”
Section: Related Work and Toolsmentioning
confidence: 99%
“…We aim at a practical and effective approach to accept privacy policies through the offered button. As previously said, most users will indeed be nudged in this direction, being the opt-out options often made cumbersome on purpose [18,27,33].…”
Section: Priv-accept Design and Testingmentioning
confidence: 99%